2010
DOI: 10.1128/aac.00751-10
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of Hydrogen Peroxide, an Effective Disinfection System via Hydroxyl Radical Formation

Abstract: The relationship between the amount of hydroxyl radicals generated by photolysis of H 2 O 2 and bactericidal activity was examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
110
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 157 publications
(114 citation statements)
references
References 29 publications
3
110
1
Order By: Relevance
“…Later, the AOP concept has been extended to the oxidative processes with sulfate radicals (SO 4 have too short half-life (on the order of microseconds), so that the required detention times for disinfection are prohibitive due to extremely low radical concentrations [5]. When AOPs are applied for wastewater treatment, these radicals, as a powerful oxidizing agent, are expected to sufficiently destruct wastewater pollutants, and transform them to less and even non-toxic products, thereby providing an ultimate solution for wastewater treatment [6].…”
Section: Advanced Oxidation Processesmentioning
confidence: 99%
“…Later, the AOP concept has been extended to the oxidative processes with sulfate radicals (SO 4 have too short half-life (on the order of microseconds), so that the required detention times for disinfection are prohibitive due to extremely low radical concentrations [5]. When AOPs are applied for wastewater treatment, these radicals, as a powerful oxidizing agent, are expected to sufficiently destruct wastewater pollutants, and transform them to less and even non-toxic products, thereby providing an ultimate solution for wastewater treatment [6].…”
Section: Advanced Oxidation Processesmentioning
confidence: 99%
“…Nonetheless, the total amount of ÁOH generated in 20 min was estimated to be approximately 169 lM. Our previous result using photolysis of H 2 O 2 as an ÁOH generation system suggested that 200-300 lM ÁOH yielded within 3 min would be needed to produce a [5-log reduction in S. aureus (Ikai et al 2010). Thus, the amount of ÁOH obtained in the present study would be sufficient to kill the bacteria within 20 min.…”
Section: Esr Analysis Of áOh and Colorimetric Determination Of H 2 Omentioning
confidence: 79%
“…• is also an ROS and has one unpaired electron in its structure, so it is apt to deprive other substances of an electron, thus oxidizing them (15). This makes HO…”
Section: Introductionmentioning
confidence: 99%